"Just Follow the Lights": A Ubiquitous Framework for Low-Cost, Mixed Fidelity Navigation in Indoor Built Environments. Issue 155 (November 2021) - Dasler, Philip; Malik, Sana; Mauriello, Matthew Louis
Highlights: A low-cost system for indoor navigation with a lightweight and open deployment paradigm as well as a novel map ingestion mechanism A formative study that explores current perceptions of existing navigation solutions while also reaffirming the need for additional navigational support in everyday buildings A controlled study that evaluates performance and the interaction of display density and route complexity against an existing baseline Design recommendations for deploying such systems in the built environment to foster new interactions in buildings. A system of networked LED indicators can improve both wayfinding performance and experience, boosting confidence and consistency among users while delivering similar benefits as high-cost digital alternatives. Abstract: Indoor navigation is an important daily task in a variety of contexts ( e.g., offices, hospitals, airports). However, navigational ease is not always considered when buildings are designed, making wayfinding a difficult and frustrating experience. Moreover, existing solutions are expensive, highly specialized, or both. In this work, we examine how a system of connected low-cost displays designed as an open API can be leveraged to guide users to their destinations quickly, easily, and with minimal cognitive load. Following a formative survey ( N =58), we designed: (i) a system of linked, low-fidelity indicators, (ii) a novel map ingestion mechanism for quick and easy deployment, and (iii) a framework for controlling and interacting with an ecosystem of mixed-fidelity devices. We then evaluated our system through a controlled user experiment ( N =18) that explores the impact of indicator density and route complexity on performance. Our work shows low-cost embedded indicators can improve indoor navigational experiences by delivering many of the same benefits as more costly solutions, we argue that such indicators would complement existing navigational solutions in a mixed-fidelity ecosystem, and we discuss use-cases as well as design recommendations for deploying similar systems.